ANALYSIS OF THE IMPLEMENTATION OF THE STRATEGY FOR SOCIO-ECONOMIC DEVELOPMENT OF STAVROPOL REGION UNTIL 2020 AND FOR THE PERIOD UP TO 2025 - Nikolai Tarasov (Вестник Северо-Кавказского федерального университета, 2022)
This article analyzes the results of the implementation of the Strategy for Socio-Economic Development of the Stavropol Territory. Problem areas of implementation of the Strategy are identified, its main results are explored and conclusions of achieving intermediate objectives of the Strategy are made. The estimation of the probability of achieving the objectives by 2025 is provided.